A comparative evaluation of antimicrobial efficacy of novel surfactant-based endodontic irrigant Regimen's on Enterococcus faecalis - Manikandan Ravinanthanan; Mithra N Hegde; Veena Shetty; Suchetha Kumari; Fahd Nasser Al Qahtani (Wolters Kluwer Medknow Publications, 2022)
Introduction: Irrigants play an important role in the eradication of microorganisms in the complex root canal system. Sodium hypochlorite (NaOCl), chlorhexidine (CHX), and iodine potassium iodide (IKI) have certain limitations despite their routine clinical use. Surfactant irrigants with antimicrobial properties can be a milestone in endodontics to overcome the drawbacks of conventional irrigants. The aim of this study was to evaluate the antimicrobial efficacy of surfactants in comparison with routine endodontic irrigants on Enterococcus faecalis. Materials and Methods: Primary irrigants NaOCl, CHX, IKI were prepared at concentrations of 5%, 2.5%, 2%, and 1%; while mixture of tetracycline acid and detergent (MTAD) (100%) served as control group. Surfactants such as cetrimide (CTR) and sodium dodecyl sulfate (SDS) were prepared at concentrations of 0.5%, 1%, and 2%. The direct contact assay was used to evaluate the antimicrobial efficacy after 5 min. Statistical analysis was performed using one-way ANOVA and Mann-Whitney U-test. Results: In the primary group, only 5% CHX was significant over MTAD (P < 0.05). In the surfactant group, all concentrations of CTR and SDS (except 0.5%) were significant (P < 0.05) in killing E. faecalis over MTAD. Two percent CHX in combination with 0.5% CTR and 1% SDS had an effective kill percentage over 2% CHX and MTAD alone. Conclusion: Surfactant irrigant regimens can be used as adjuncts with CHX to overcome its clinical limitations and potentiate its substantivity, thereby enhancing clinical success in endodontics.